Pengaruh Brand Equity dan Produk Terhadap Keputusan Pembelian Fiesta Chicken Nugget - Pandi Putra (Amsir Management Journal, 2021)
This study aims to determine and analyze how much influence brand equity and product decisions have on purchasing fiesta chicken nuggets at PT. Primafood International City of Parepare has. The analytical method used in this research is the method of observation, interviews, and questionnaires and the method of determining the sample using the Roscoe formula and obtained 30 totals. The analytical method used is the method of multiple linear analysis. The method of analysis used the SPSS 20 program. The results showed that there was an influence of product brand equity and purchasing decisions of Fiesta Chicken Nugget at PT. Primafood International City of Parepare. This is evidenced by the results of the calculated F statistic of 7.492 with a significance of 0.000. Because the significance value is less than 0.05 (0.000 < 0.05). The results of the R2 determinant test in this study obtained the R2 determinant of 0.935, which means that the magnitude of the influence of Brand and Product Equity on Purchase Decisions is 93.5% and the remaining 6.5% is explained by other variables not included in this variable study